2022
DOI: 10.3389/fimmu.2022.821190
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic, Selectable, Knock-in Targeting of CCR5 via CRISPR-Cas9 Mediated Homology Directed Repair Inhibits HIV-1 Replication

Abstract: Transplanting HIV-1 positive patients with hematopoietic stem cells homozygous for a 32 bp deletion in the chemokine receptor type 5 (CCR5) gene resulted in a loss of detectable HIV-1, suggesting genetically disrupting CCR5 is a promising approach for HIV-1 cure. Targeting the CCR5-locus with CRISPR-Cas9 was shown to decrease the amount of CCR5 expression and HIV-1 susceptibility in vitro as well as in vivo. Still, only the individuals homozygous for the CCR5-Δ32 frameshift mutation confer complete resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Several different types of stem cells have also been CCR5-gene edited. For instance, CRISPR-mediated CCR5 knockout was shown to be feasible in adipose stem cells (ASCs) [ 78 , 79 ]. ASCs possess hematopoietic potential [ 80 , 81 ], and as such could be used as a cellular source for therapeutic applications.…”
Section: Targeting Ccr5 Via Crispr/cas9-mediated Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different types of stem cells have also been CCR5-gene edited. For instance, CRISPR-mediated CCR5 knockout was shown to be feasible in adipose stem cells (ASCs) [ 78 , 79 ]. ASCs possess hematopoietic potential [ 80 , 81 ], and as such could be used as a cellular source for therapeutic applications.…”
Section: Targeting Ccr5 Via Crispr/cas9-mediated Genome Editingmentioning
confidence: 99%
“…Knockout confers in vitro resistance to HIV infection in differentiated macrophages [74] Multi-lineage differentiation in vitro [53] Minimal off-target modifications detected Multi-lineage engraftment potential in animal model [82] Multi-lineage engraftment potential in animal model In vivo resistance to HIV infection [57] Multi-lineage engraftment potential after autologous HSC transplantation Persistence of low frequencies of CCR5 knockout CD4 + T cells [66] iPSCs No off-target modifications detected iPSC-derived monocytes/macrophages resistant to HIV infection [83][84][85] Primary CD4 + T cells Low transduction efficiency with lentiviral vectors [52] Knockout confers in vitro resistance to HIV infection [24,52,53,74] Introduction of ∆32/∆32 mutation No off-target modifications detected [51] Macrophage or T cell cell-lines CRISPR-mediated KO feasible [78,86,87] Introduction of ∆32/∆32 mutation High fidelity screening method [77] This was expanded upon by Xu et al, where also in an in vivo animal model resistance to HIV infection was observed after CCR5-knockout HSC engraft generated via CRISPR/Cas9 [57]. As discussed, autologous CRISPR-edited CCR5 knockout HSCs have also been successfully transplanted in a patient with HIV and acute lymphocytic leukemia [66].…”
Section: Hscsmentioning
confidence: 99%
“…Furthermore, as with eFlut, the modified cells express foreign genes. In another application of marker gene selection, Scheller et al used two donor DNAs with different fluorescent protein-expressing selection cassettes to interrupt the CCR5 gene, a co-receptor for HIV-1, making the cells resistant to HIV-1 infection [ 53 ]. Selecting for double-positive cells ensures that the gene editing is biallelic.…”
Section: Selecting Edited Cellsmentioning
confidence: 99%
“…Targeting CCR5 expression via CRISPR/Cas9 mediated HDR in four cell lines, including freshly healthy human cells, dramatically suppressed HIV-1 replication. Indeed, the generated cells that are highly deficient in CCR5 showed resistance to HIV-1 infection ( Scheller et al., 2022 ).…”
Section: Applications Of Crispr/cas Technology In Targeting Viral And...mentioning
confidence: 99%